Huoshan Dendrobium Zengye Jiedu Formula mitigates radiation-induced oral mucositis and improves oral immune microenvironment by targeting the EGFR/PI3K/AKT pathway: evidence from network pharmacology, molecular docking, and experimental validation - Liu, Chang; Liu, Xinru; Liu, Jiabao; Zhang, Hao; Zhang, Pengcheng; Huo, Xingxing; Song, Hang; Zhu, Yongfu (Frontiers in Immunology, 2025)
IntroductionRadiation-induced oral mucositis (RIOM) manifests as mucosal ulceration, pain, and dysphagia, disrupting treatment and quality of life. Its pathogenesis involves inflammatory imbalance and immune dysregulation, driven by microbial infiltration and cytokine storms. Current therapies remain inadequate, necessitating deeper exploration of immune-microbial interactions for effective interventions.MethodsBioactive components of Huoshan Dendrobium Zengye Jiedu Formula (HDZJF) and RIOM-related targets were retrieved from public databases. Core therapeutic targets and pathways were systematically analyzed via protein-protein interaction (PPI) networks, Gene Ontology (GO), and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment. Molecular docking evaluated interactions between HDZJF components and key targets. A rat RIOM model validated HDZJF efficacy by assessing mucositis severity, inflammatory cytokines, and EGFR/PI3K/AKT pathway protein expression.ResultsA total of 102 bioactive components and 379 potential targets for RIOM were identified. GO and KEGG enrichment analyses suggest that HDZJF exerts therapeutic effects on RIOM by modulating processes such as angiogenesis, inflammation, and apoptosis through pathways like PI3K-AKT. Molecular docking confirmed strong binding affinities between HDZJF components and key targets. In vivo, HDZJF reduced inflammation, promoted mucosal healing, improved body weight, and modulated protein expression related to EGFR/PI3K/AKT.DiscussionThe findings highlight HDZJF's capacity to alleviate RIOM by targeting the EGFR/PI3K/AKT pathway, thereby suppressing inflammatory responses and apoptotic processes. These results underscore HDZJF's translational potential for RIOM treatment and justify further clinical investigation into its therapeutic utility.